2014
DOI: 10.1371/journal.pone.0111063
|View full text |Cite
|
Sign up to set email alerts
|

The Mpumalanga Men's Study (MPMS): Results of a Baseline Biological and Behavioral HIV Surveillance Survey in Two MSM Communities in South Africa

Abstract: The Mpumalanga Men's Study (MPMS) is the assessment of the Project Boithato HIV prevention intervention for South African MSM. Boithato aims to increase consistent condom use, regular testing for HIV-negative MSM, and linkage to care for HIV-positive MSM. The MPMS baseline examined HIV prevalence and associated risk behaviors, and testing, care, and treatment behaviors among MSM in Gert Sibande and Ehlanzeni districts in Mpumalanga province, South Africa in order to effectively target intervention activities. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
72
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 36 publications
1
72
0
Order By: Relevance
“…In terms of demographics, South African MSM older than 25 have consistently been found to have higher HIV infection rates than other MSM (Baral et al, 2011;Lane et al, 2011;Sandfort, Knox, Collier, Lane, & Reddy, 2015). Psychosocial factors contributing to HIV risk include: sexual self-identity (Lane et al, , 2014Rispel et al, 2011;Sandfort, Lane, Dolezal, & Reddy, 2015); experiences of stigma and homophobia (Arnold, Struthers, McIntyre, & Lane, 2013;Tucker et al, 2014); low self-efficacy for protective behaviours (Tucker et al, 2014); beliefs about trust and condom use in relationships (Knox, Yi, Reddy, Maimane, & Sandfort, 2010); being in a relationship with a regular partner (Arnold et al, 2013;Knox et al, 2010); and experiencing depression (Tucker et al, 2013). Behavioural risk factors for HIV infection identified in previous research include: transactional sex Nel, Yi, Sandfort, & Rich, 2013); high numbers of sexual partners Tucker et al, 2014); and alcohol and drug use Lane, Shade, McIntyre, & Morin, 2008;Parry et al, 2008;Sandfort, Yi, Knox, & Reddy, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of demographics, South African MSM older than 25 have consistently been found to have higher HIV infection rates than other MSM (Baral et al, 2011;Lane et al, 2011;Sandfort, Knox, Collier, Lane, & Reddy, 2015). Psychosocial factors contributing to HIV risk include: sexual self-identity (Lane et al, , 2014Rispel et al, 2011;Sandfort, Lane, Dolezal, & Reddy, 2015); experiences of stigma and homophobia (Arnold, Struthers, McIntyre, & Lane, 2013;Tucker et al, 2014); low self-efficacy for protective behaviours (Tucker et al, 2014); beliefs about trust and condom use in relationships (Knox, Yi, Reddy, Maimane, & Sandfort, 2010); being in a relationship with a regular partner (Arnold et al, 2013;Knox et al, 2010); and experiencing depression (Tucker et al, 2013). Behavioural risk factors for HIV infection identified in previous research include: transactional sex Nel, Yi, Sandfort, & Rich, 2013); high numbers of sexual partners Tucker et al, 2014); and alcohol and drug use Lane, Shade, McIntyre, & Morin, 2008;Parry et al, 2008;Sandfort, Yi, Knox, & Reddy, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This means that HIV prevention efforts developed in urban contexts may need to be adapted based on the relative importance of particular risk factors. Potentially important features of the rural context that may affect HIV risk among MSM include: the relative importance of traditional cultural beliefs and practices (Icard et al, 2015); high rates of poverty and unemployment (Neves & du Toit, 2013;Pronyk et al, 2008); high levels of circular migration between urban and rural areas (Hunter, 2010;Neves & du Toit, 2013;Pronyk et al, 2008); and lower levels of educational attainment (Lane et al, 2014). Based on findings among urban and peri-urban MSM, the relatively higher rates of rural unemployment, and lower levels of formal education in rural South Africa may have a disproportionate effect on HIV risk among MSM in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…25 Simultaneously, the progress and momentum in South Africa are encouraging; it is the only country in sub-Saharan Africa where gay rights are formally recognized, and national policies emphasized reducing discrimination based on sexual orientation. 26 Men who have sex with men were included for the first time in the 2007 to 2011 National Strategic Plan for HIV, and the South African government has developed specific efforts and resources to combat HIV among MSM, 15,19 including promotion of PrEP and routine HIV testing. 15 One promising approach to HIV prevention is the creation of combination prevention packages that conglomerate individually efficacious HIV-prevention measures into 1 package, which is targeted specifically to the unique needs and risks of a given population.…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 16.3% to 20.6% of MSM have undiagnosed HIV infection in this setting, complementing different studies with MSM in other African communities that have shown similar high rates of undiagnosed HIV infection. [3][4][5] In this rural setting, 1 in 2 MSM over the age of 25 years are HIV positive with only 18.3% linked to care and 13.6% taking antiretroviral treatment (ART). 3 Although we have good understanding of HIV risk for MSM in African settings, we have limited understanding of HIV risk factors and health-care needs for transgender individuals.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In this rural setting, 1 in 2 MSM over the age of 25 years are HIV positive with only 18.3% linked to care and 13.6% taking antiretroviral treatment (ART). 3 Although we have good understanding of HIV risk for MSM in African settings, we have limited understanding of HIV risk factors and health-care needs for transgender individuals. [6][7][8][9] In general, there have been few, and only recent, HIV prevention activities with rural MSM and transgender African communities.…”
Section: Introductionmentioning
confidence: 99%